Preliminary investigation of a possible dose rate effect on survival of cells irradiated with low energy protons - Robinson, L P G (Department of Physics, 2017)
Apparatus has been developed for the irradiation of V79-379A Chinese hamster lung fibroblast cells with 3.6 MeV protons from the Van de Graaff accelerator at the National Accelerator Centre in Faure. The original intention of this work was to investigate and measure a possible dose rate effect on the survival of V79 cells, in the dose range from zero to 25 Gy, at dose rates of about 3 Gy/s and 300 Gy/s. The survival curves initially obtained were anomalous in that they showed abnormally high levels of survival and a tendency to remain at a constant survival level for doses above 10 Gy. Systematic attempts to correct this observed anomaly, involved the following; apparatus improvements were made, a means of measuring the beam profile was devised, the current measuring device and the dosimetry were improved and a possible dose rate effect on intracellular oxygen was investigated. After these improvements, the anomalous effect was much reduced, but not entirely eliminated. The final results showed no significant difference between the survival of cells irradiated at dose rates of about 3 Gy/s and 300 Gy/s; qualitative differences were however noticeable. After correction for the effect of a non-uniform beam profile, the survival curves were significantly different to published work. This difference suggested a possible dose rate effect between dose rates of about 0.1 Gy/s and dose rates above 3 Gy/s.